Current Concepts and Approaches to Development of Transport Engineering Enterprises - A. D. Bezdelov (Вестник Российского экономического университета имени Г. В. Плеханова, 2025)
The research has enriched theoretical base of developing enterprises of transport machine-building, which includes systematization of principle stages of industry development, identification of key events and their after-effects and it can demonstrate higher rates and frequency of new technology arising that transforms approaches and strategies of transport engineering progressing. The article studies classifications of today’s concepts and approaches to the development of transport machine-building by groups that differ from each other in priority trends of managing enterprises of this industry and other industries of economy. The research shows that it is possible to find differences in approaches to management of transport engineering between Russian scientists and experts and their foreign colleagues, which can be connected with cultural and political characteristics of the present development of countries, however, the global trend on wider use of innovation technologies, such as business digitalization, automation of processes, new materials, approaches to organizational structure, etc. is still retained. Leading companies and research institutes keep working at introduction of AI, the Internet of things and blockchain technologies to optimize logistic chains and management of transportation stock.